Social Media and Criminal Responsibility: A Case Report - Ünver, Hatice; Şimşek, Nurcan Eren; Olgun, Nesligül Nihal; Şahin, Ayhan; Şişmanlar, Şahika Gülen; Coşkun, Ayşen; Biçer, Ümit (The Bulletin of Legal Medicine, 2016)
Criminal responsibility is based on that when a person committed a crime he has full consciousness and will. There are many factors which diminish or abolish the criminal responsibility. Countries set different age limits in relation with the age of criminal responsibility, legally. In our country, criminal responsibility is accepted us full after the end of 15s if detected no mental illness or weakness, but between 12-15 years of age it should be evaluated understanding of the legal meaning and consequences of the crime. This assessment which wanted to done in a certain age bracket is expected to search primarily the effects of developmental characteristics on criminal responsibility. In addition, an approach which evaluates mental disorders, medical diseases and social environment where the child is linked to will provide a holistic perspective on the biopsychosocial aspects. On the other hand, crimes related the social media had become more discussed due to development of technology and widespread use of internet.In this case report, it is reviewed that forensic psychiatric evaluation reporting process of a 15-years-old adolescent who was claimed to offence to a public official through social media, and wanted to be evaluated about criminal responsibility and forensic psychiatric evaluation method will be discussed.It is known that usage of social media among adolescents has been increasing, recently. We want to take attention on this issue, due to the increment of forensic psychiatric assessment of adolescent, claimed to offence crimes related to social media.
Keywords: social media; criminal responsibility; child and adolescent